Un paseo entre los museos. Julio Cortázar en Italia (El Hilo de la Fabula, 2025)
This article aims to approach Julio Cortázar's work by studying the intrinsic fecundity of the influence of an elementary model in his work: the museum, which constituted a fundamental intertext in his writings. It will examine his work in a precise place and during a specific period: between 1953 and 1954, when the writer was able to assimilate the textual and paratextual system of the Italian museums he visited assiduously during his stay in that country, always in search of new semiotic systems capable of exceeding the traditional boundaries of literature.